2019
DOI: 10.21475/ajcs.19.13.01.p1109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of agronomical and morphological traits contributing to drought stress tolerance in soybean

Abstract: Abiotic stresses, especially drought, may seriously affect soybean yield. Due to the complexity of drought tolerance, one of the difficulties in selecting genotypes is the identification of traits contributing to improve stress tolerance. This study carried out soybean phenotyping under water deficit in vegetative and reproductive stages in field conditions at two consecutive crop seasons (2012/13 and 2013/14). The experiment was performed in Londrina, PR, Brazil, with two soybean cultivars with distinct level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
(17 reference statements)
2
18
2
1
Order By: Relevance
“…An unexpected result of the present work was the increased HI under drought stress. Contrary to this, reduced HI under drought stress has been reported in maize ( Earl and Davis, 2003 ) and soybean ( Oya et al, 2004 ; Giordani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…An unexpected result of the present work was the increased HI under drought stress. Contrary to this, reduced HI under drought stress has been reported in maize ( Earl and Davis, 2003 ) and soybean ( Oya et al, 2004 ; Giordani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 87%
“…Even in unusually wet years, soybean yields in Ontario are reduced by transient soil water deficits, and in drier years, yield losses may exceed 25% (H. J. Earl, unpublished data). Numerous controlled environment and field studies have also reported yield reductions ranging from 24 to 80% in soybean subjected to different levels of drought stress (e.g., Frederick et al, 2001 ; Sadeghipour and Abbasi, 2012 ; He et al, 2016 , 2017 ; Wei et al, 2018 ; Giordani et al, 2019 ; Gebre, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Selection methods for several environments are always of interest to soya bean breeders (Füzy et al, 2019;Giordani et al, 2019;Vianna et al, 2019) and other crops of economic interest (Mazengo, Tryphone, & Tarimo, 2019;Ramzan, Aslam, Ahsan, & Awan, 2019), attributed mainly by the strong G × E interaction that occurs in most crops and the changing conditions found in the field (abiotic and biotic stresses), which contribute to the decreased performance of several genotypes across environments.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…To manage and understand these variations when evaluating a relatively large set of genotypes, as well as several stresses at the same time, it is necessary to employ appropriate techniques for this purpose. Techniques such as PCA (principal component analysis) (Füzy et al, 2019;Giordani et al, 2019;Ramzan et al, 2019), ranking (Mazengo et al, 2019), BLUP (best linear unbiased prediction) (Nardino et al, 2016;Olivoto et al, 2017), AMMI (additive main effects and multiplicative interaction) (Bocianowski, Niemann, & Nowosad, 2019;Veenstra, Santantonio, Jannink, & Sorrells, 2019), and the combination of BLUP and AMMI (Olivoto, Lúcio, Silva, Marchioro, et al, 2019) and MTSI (multi-trait stability index) (Olivoto, Lúcio, Silva, Sari, et al, 2019) have been employed.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Due to the drought tolerance complexity, most breeders are still using total yield, yield stability (Giordani et al., 2019), or traits that have been associated with yield stability, such as canopy wilting (Ye et al., 2020) and root structure (Pantalone et al., 1996; Prince et al., 2015), as an indirect selection for drought tolerance. To evaluate yield stability, several authors have developed drought susceptibility indices (DSIs), based on a regression coefficient between contrasting environments (i.e., irrigated vs. nonirrigated conditions) (Clarke et al., 1992; Fischer & Maurer, 1978 ).…”
Section: Introductionmentioning
confidence: 99%